Mana whenua engagement in Crown and Local Authority‐initiated environmental planning processes: A critique based on the perspectives of Ngāi Tahu environmental kaitiaki. (1st August 2021) - Bennett, Courtney; Matunga, Hirini; Steyl, Steven; Borell, Phillip; Dionisio, Rita; Hāpuku, Aaron
Abstract: In New Zealand, the Crown and Local Authorities are required to engage with iwi in resource management matters, yet iwi engagement is a widely recognised weakness in many resource management professionals' skillsets. Coloniality permeates many interactions with iwi, and reflects a profession where practitioners' skillsets have not kept pace with developments in resource management legislation that better recognise the rights and interests of mana whenua. This article explores the real‐life impacts of this skill paucity on Ngāi Tahu environmental kaitiaki, and, through a Braided River methodological approach comprised of Kaupapa Māori research and Narrative Inquiry, offers recommendations for best practice mana whenua engagement. The article concludes by discussing the coloniality of planning, and how this impacts practitioners' ability to implement these best practice recommendations.